Effect of Inhibitor Addition, pH, and Current Density on the Corrosion Rate of Fe Metals - Anisa Fatma Aulia; Nurul Faizah; Rizal Arifin; Ardista Izdhihar Kaloka; Gladys Sukma Thufailah (Institut Teknologi Sepuluh Nopember, 2025)
Corrosion significantly impacts public safety and the economy, causing substantial financial losses, infrastructure damage, and hazardous incidents across various industries. Researchers investigated the effects of pH, current density, and corrosion inhibitors (potassium chromate and potassium nitrate) on iron corrosion by measuring weight loss of iron samples immersed in sulfuric acid over time. The addition of inhibitors showed that KNO3 was more effective in reducing the corrosion rate, with values of 4.992068, 3.744051, 2.736034, 1.728017, and 0.608008 mils per year, compared to K2CrO4, which resulted in 9.728132, 7.296099, 5.472066, 3.648033, and 1.216017 mils per year. Corrosion rate increased as pH decreased, with Fe showing corrosion at pH 6.21, 5.18, 4.26, 3.85, and 3.22. The relationship between current density and corrosion rate was found to be proportional, with voltage values of 1.31, 2.24, 3.16, 5.11, and 7.1 amperes per square meter (A/m^2). This study confirms that inhibitor type, acidity (pH), and current density significantly influence corrosion behavior, where increasing pH and current density can accelerate corrosion, and potassium nitrate (KNO3) demonstrates superior corrosion inhibition compared to potassium chromate (K2CrO4).